Building on Experience: a formative evaluation of a peer education sexual health project in South Africa. (1st July 2004) - Warwick, Ian; Aggleton, Peter
Abstract : In South Africa, as elsewhere in the world, the promise of peer education as a means of promoting sexual health has contributed to its increasing popularity. While structural and organisational constraints can compromise the success of peer education, many of those involved in modest local programmes in South Africa are able to address the sexual health and well-being of young people through knowing about and making the most of proximal salutogenic factors—personal qualities and local contextual characteristics that influence health. Participatory formative evaluation can contribute to the development of peer education practice by providing opportunities for educators to extend their pedagogic knowledge and skills and review and re-orient their work. However, to embed new ways of working, sustained partnerships will be necessary.